Muscle ultrasonography to predict survival in amyotrophic lateral sclerosis. Issue 5 (14th April 2010) - Arts, Ilse MP; Overeem, Sebastiaan; Pillen, Sigrid; Schelhaas, Helenius Jurgen; Zwarts, Machiel J
Abstract : The authors assessed the prognostic value of muscle ultrasonography in 31 patients with amyotrophic lateral sclerosis (ALS) and compared it with accepted prognostic variables like functional capacity (measured with the Amyotrophic Lateral Sclerosis Functional Rating Scale (ALSFRS)) and muscle strength. Each patient was examined once. The following ultrasonography parameters were determined: muscle thickness, echo intensity (EI) and the presence of fasciculations. Correlations between baseline measurements, preslope values and survival were calculated. EI, disease duration, muscle strength preslope and ALSFRS-R preslope correlated with survival. Using a stepwise multivariate analysis, the combination of EI preslope and ALSFRS-R preslope was shown to have the best predictive value for survival.